Estriol blunts postprandial blood glucose rise in male rats through regulating intestinal glucose transporters - Yamabe, Noriko (Am J Physiol Endocrinol Metab, 2014)
Despite increased total food intake in healthy, late-stage pregnant women, their peak postprandial blood sugar levels are normally much lower than the levels seen in healthy nonpregnant women. In this study, we sought to determine whether estriol (E(3)), an endogenous estrogen predominantly produced during human pregnancy, contributes to the regulation of the postprandial blood glucose level in healthy normal rats. In vivo studies using rats showed that E(3) blunted the speed and magnitude of the blood glucose rise following oral glucose administration, but it did not appear to affect the total amount of glucose absorbed. E(3) also did not affect insulin secretion, but it significantly reduced the rate of intestinal glucose transport compared with vehicle-treated animals. Consistent with this finding, expression of the sodium-dependent glucose transporter 1 and 2 was significantly downregulated by E(3) treatment in the brush-border membrane and basolateral membrane, respectively, of enterocytes. Most of the observed in vivo effects were noticeably stronger with E(3) than with 17β-estradiol. Using differentiated human Caco-2 enterocyte monolayer culture as an in vitro model, we confirmed that E(3) at physiologically relevant concentrations could directly inhibit glucose uptake via suppression of glucose transporter 2 expression, whereas 17β-estradiol did not have a similar effect. Collectively, these data showed that E(3) can blunt the postprandial glycemic surge in rats through modulating the level of intestinal glucose transporters.